Assessment of impact of a novel infectious bursal disease (IBD) vaccination programme in breeders on IBD humoral antibody levels through the laying period. Issue 1 (26th June 2014) - Parker, Daniel; de Wit, Sjaak; Houghton, Helen; Prandini, Francesco
Abstract : Objectives: The purpose of this study was to assess whether broiler breeders vaccinated in ovo with a Vaxxitek (HVT&IBD) (Merial) plus an inactivated IBD vaccine prior to the onset of lay had a significantly different humoral IBD antibody response to broiler breeders vaccinated solely with Vaxxitek (HVT&IBD) (Merial) in ovo. In addition, maternally derived antibody (MDA) passed to the progeny of these two breeders flocks was also compared at three time points during lay. Design: The study was a case–control study where the two flocks were the same breed, reared on the same farm and transferred to the same laying farm, the only difference between the flocks being the IBD vaccination programme. The humoral IBD antibody response in the flocks and their progeny was measured using two commercial ELISA tests and a serum neutralisation (SN) test. Results: There was no significant difference (P<0.05) in the humoral IBD antibody response in the two breeder flocks as measured by ELISA test except at a single time point at 22 weeks when measured by BioChek ELISA and at 60 weeks when measured by IDEXX ELISA. There was no significant difference (P<0.05) in the humoral IBD antibody response in the two breeder flocks as measured by SN test except at 27 and 55 weeks. There was no significant difference (P<0.05) in the levels of MDA passed to progeny of these two breeder flocks as measured by ELISA or SN test. Conclusions: It is proposed that a single vaccination with Vaxxitek (HVT&IBD) (Merial) will provide a similar level of IBD protection to breeders and their progeny as a Vaxxitek (HVT&IBD) (Merial) plus inactivated IBD vaccine, vaccination programme. This novel IBD vaccine provides additional options for vaccination programmes for broiler breeders without impacting on the protection of the broiler progeny.